Intraoperative Determination of the Actual Length of the Small and Large Intestine and its Relation to Anthropometric Variables in the Egyptian Population (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: bowel; anthropometric variables; total small bowel length (TSBL); egyptian population